2019
DOI: 10.2478/adms-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Orbital TIG Welding of Titanium Tubes with Perforated Bottom Made of Titanium-Clad Steel

Abstract: The article presents problems accompanying the industrial TIG welding (142) of a heat exchanger perforated bottom made of steel clad with titanium B265 grade 1 with tubes made of titanium B338 grade 2. Research-related tests involved the making of test plates containing simulated imperfections formed during orbital welding. The above-named imperfections resulted from insufficient gas shielding during the welding process, the improper positioning of the tungsten electrode (excessively large or overly small circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In the earth’s crust it occurs in the form of minerals such as titanite, anatase, ilmenite, brookite, perovskite and rutile, with a content of only 0.61% (the ninth most abundant element) [ 1 ]. The pure metal and its alloys have a wide range of applications in many areas, inter alia: biomedical, chemical, offshore, transportation (aviation and automotive), energy and recreation [ 2 , 3 , 4 , 5 ]. Titanium is completely resistant to moist hydrochloric acid, nitric acid, chlorine compounds, sulfides, sulfur, ammonia and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…In the earth’s crust it occurs in the form of minerals such as titanite, anatase, ilmenite, brookite, perovskite and rutile, with a content of only 0.61% (the ninth most abundant element) [ 1 ]. The pure metal and its alloys have a wide range of applications in many areas, inter alia: biomedical, chemical, offshore, transportation (aviation and automotive), energy and recreation [ 2 , 3 , 4 , 5 ]. Titanium is completely resistant to moist hydrochloric acid, nitric acid, chlorine compounds, sulfides, sulfur, ammonia and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [27] conducted by the Authors showed that in order to ensure the quality of the connection of titanium pipes with the perforated bottom, it is necessary to constantly control the welding process. During the industrial process, there may be defects associated with inadequate shielding of the protective gas, incorrect positioning of the tungsten electrode (on too large or small track circumference), too high speed of electrode movement resulting from an incorrectly set welding program, as well as too high current during welding.…”
Section: Discussionmentioning
confidence: 99%
“…After an experiment of welding of 304L austenitic stainless steel/Incoloy 800HT nickel alloy, it was found that the joint had good mechanical and microstructural attributes as compared with the base metal parts [24]. The orbital TIG welded titanium tubes with bottom made up of Ti-clad steel showed a satisfactory result when tested under non-destructive and macrographic tests [25]. The hydroxyapatite coating was performed on laser modified Ti13Nb13Zr alloy by using electrophoretic deposition.…”
Section: Introductionmentioning
confidence: 99%